Detection of eccentricity in silver nanotubes by means of induced optical forces and torques - Abraham, Ricardo Martín (2015)
In previous works (Abraham et al 2011 Plasmonics 6 435; Abraham Ekeroth and Lester 2012 Plasmonics 7 579; Abraham Ekeroth and Lester 2013 Plasmonics 8 1417; Abraham Ekeroth R M and Lester M 2015 Plasmonics 10 989–98), we have conducted an exhaustive study about optical properties of metallic realistic two-dimensional (2D) nanotubes, using an experimental-interpolated dielectric function (Palik 1985 Handbook of Optical Constants of Solids (Toronto: Academic Press)). In the case of non-homogeneous metallic shells, we suggested (in a theoretical form) a procedure to detect the non-uniformity of shells in parallel, disperse and randomly oriented long nanotubes (2D system). This detection is based exclusively on the plasmonic properties of the response (Abraham Ekeroth and Lester 2012 Plasmonics 7 579). Here we consider exact calculations of forces and torques, exerted by light on these kinds of nanostructures, illustrating the mechanical effects of plasmonic excitations with one example of silver shell under p-polarized incidence. This study continues with the methodology implemented in the previous paper (Abraham Ekeroth R M and Lester M 2015 Plasmonics 10 989–98), for homogeneous nanotubes. The features of the electromagnetic interaction in these structures, from the point of view of mechanical magnitudes, make it possible to conceive new possible interesting applications. Particularly, we point out some results regarding detection of eccentricity in nanotubes in vacuum (when Brownian movement is not taken into account). We interpret the optical response of the realistic shells in the framework of plasmon hybridization model (PHM), which is deduced from a quasi-static approximation. Our integral formalism provides for retardation effects and possible errors is only due to its numerical implementation.